2013
DOI: 10.1021/jo400737f
|View full text |Cite
|
Sign up to set email alerts
|

Two Approaches to the Aromatic Core of the Aminonaphthoquinone Antibiotics

Abstract: Two complementary approaches are presented for the synthesis of the quinone chromophores of the naphthoquinone ansamycins and related natural products. The first involves the use of an improved protocol for the manganese(III) acetate mediated cyclization of 5-aryl-1,3-dicarbonyl compounds to β-naphthols, leading to the simple, scalable preparation of building blocks suitable for the synthesis of naturally occurring aminonaphthoquinones. The second approach involves the Diels-Alder reaction of a series of new, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Batatasin-III (1) was purchased (>99 % purity determined by HPLC) from Paragon Biochemical LLC (Salt Lake City, United States of America). Wittig salts were prepared according to the protocols of Chalal et al 57 3-Benzyloxy-5-methoxybenzyl bromide was synthesized by the method of Nawrat et al 58 Diethyl 3,5-dibenzyloxybenzylphosphonate was prepared according to the protocol of Sun et al 59 Marine Organisms. Four pure, but non-axenic, marine microalgae (obtained from Algobank, Caen, France) and ten marine bacterial strains were used in the current study (Table 6).…”
Section: Methodsmentioning
confidence: 99%
“…Batatasin-III (1) was purchased (>99 % purity determined by HPLC) from Paragon Biochemical LLC (Salt Lake City, United States of America). Wittig salts were prepared according to the protocols of Chalal et al 57 3-Benzyloxy-5-methoxybenzyl bromide was synthesized by the method of Nawrat et al 58 Diethyl 3,5-dibenzyloxybenzylphosphonate was prepared according to the protocol of Sun et al 59 Marine Organisms. Four pure, but non-axenic, marine microalgae (obtained from Algobank, Caen, France) and ten marine bacterial strains were used in the current study (Table 6).…”
Section: Methodsmentioning
confidence: 99%
“…Reduction of 11 with LiAlH 4 , followed by benzylic bromination assisted by PBr 3 in dioxane provided bromide 12 in almost quantitative yield over two steps. 12 To insert the stable enolate fragment, nucleophilic substitution of 12 with the carbanion formed from previously prepared N-Boc malonate 14 with Cs 2 CO 3 gave desired alkylated product 15 in 80% isolated yield. Another alkylation protocol using microwave irradiation at high temperature was applied; 13 however, in this case, we observed that the Boc group from 14 is heat sensitive, and a decrease in the isolated yield was observed.…”
Section: Bischler-napieralski Pathwaymentioning
confidence: 99%
“…Among all kinds of quinone, 2-aminonaphthoquinone moiety is an integral part of antibiotic drugs or naturally occurring quinone compounds [51] synthesized by nature under ambient conditions. [52,53] Severe conditions are necessary for their synthesis on the laboratory scale, [54] with their formation usually facilitated via several intermediates wherein the 1,4-naphthoquinone moiety serves as electrophile. [55] The reactions involving 1,4-naphthoquinones as the substrate may lead to the formation of unexpected products; few reactions are enlisted as Diels-Alder cycloaddition reaction of bis-xanthene [56] to 1,4-naphthoquinone, regioselectivity in dimerization during the synthesis of pyronaphthoquinones, ventiloquinone L [57] in the presence of cerium ammonium nitrate, [58] reactions between 5,7-dihydroxynaphthoquinone and nucleophiles [59] aryl-aryl coupling [60] in 6-bromo-1,2-naphthoquinone reactions, are some examples of unexpected reactions.…”
Section: Introductionmentioning
confidence: 99%